PENGARUH PENGGUNAAN MEDIA QUIZLET DAN MIME GAME TERHADAP PENGUASAAN KOSAKATA DESCRIPTIVE TEXT SISWA KELAS VII - Okti Setianingsih; Yoga Prihatin; Sutji Muljani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effect of using Quizlet and Mime Game as learning media on the vocabulary mastery of descriptive texts among seventh-grade students at SMP Negeri 1 Kedungbanteng. The research was motivated by the low level of student interest and achievement in learning English, particularly in vocabulary acquisition. The method employed was a quasi-experimental design with a pretest-posttest control group. The research sample consisted of two classes, each assigned to use either Quizlet or Mime Game during the learning process. The results indicated that both media significantly improved students’ vocabulary mastery. However, students who learned using Quizlet showed statistically higher achievement compared to those in the Mime Game group. These findings suggest that integrating digital-based learning media like Quizlet and game-based media like Mime Game can serve as effective alternative teaching strategies. The use of such media not only enhances student engagement in the learning process but also positively impacts English learning outcomes, especially in the area of vocabulary mastery.